Hsa_circ_0074158 regulates the endothelial barrier function in sepsis and its potential value as a biomarker - Liao, Haiyan; Chai, Yan; Sun, Yuming; Guo, Zhe; Wang, Xuesong; Wang, Ziyi; Wang, Ziwen; Wang, Zhong (Frontiers in Genetics, 2022)
Background: Sepsis is one of the main causes of death in critically ill patients with high morbidity and mortality. Circular RNAs (CircRNAs) are aberrantly expressed, and play significant regulatory roles in many diseases. However, the expression profiles and functions of circRNAs in sepsis have not yet been fully clarified. Methods: Our present study performed an RNA sequencing (RNA-seq) analysis to assess the expression profiles of circRNAs in vitro. We applied the quantitative real-time polymerase chain reaction (RT-qPCR) to verify the RNA-seq results. The analyses of Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, the competitive endogenous RNA (ceRNA) regulatory networks, were performed to explore the potential mechanism in sepsis. And then, significantly up-regulated differentially expressed (DE) circRNA, hsa_circ_0074158, was selected for further study. Hsa_circ_0074158 was silenced to investigate its regulatory function in sepsis, and the barrier function was also examined in vitro. Endothelial cell junctions were valued using Vascular endothelial cadherin (VE-cadherin), which was detected by immunofluorescence staining. We measured endothelial permeability by transendothelial electrical resistance (TEER) and fluorescein isothiocyanate (FITC)-dextran extravasation. Results: In total, 203 significantly DE circRNAs, including 77 up-regulated and 126 down-regulated, were identified. In vitro, the RT-qPCR assay showed that the expression pattern of hsa_circ_0074158, hsa_circ_RSBN1L_11059, hsa_circ_0004188, and hsa_circ_0005564 were consistent with the results from RNA-seq analysis. The expression of hsa_circ_0074158 detected by RT-qPCR in vivo was also consistent with the RNA-seq results. The ceRNA networks, GO enrichment, and the KEGG pathway analyses revealed that circRNAs may be related to the barrier function in sepsis. The immunofluorescence assay showed that the suppression of hsa_circ_0074158 expression significantly enhanced the expression of VE-cadherin, which was suppressed in lipopolysaccharide (LPS)-induced sepsis. Additionally, hsa_circ_0074158 knockdown could partially reverse the LPS-induced TEER reduction and FITC-dextran extravasation elevation in sepsis. Conclusions In conclusion, we have found DE circRNAs could serve as potential biomarkers and therapeutic targets for sepsis. Hsa_circ_0074158 plays a vital role in sepsis and is related to the disruption of the endothelial barrier.